Institutional Environment for the Formation of the Soviet Generation - Yu. Tsohla, S.; A. Simchenko, N.; P. Chyvatkin, P. (International Journal of Engineering and Technology, 2018)
In the current context of dominating threats to the Russian national security, the issues of national identity and citizens' involvement in the history and culture of Russia acquire particular relevance and significance. This article reveals the essence of the cause-and-effect relationships, which played a key role in the formation of personality and socialization of the Soviet generation. The authors managed to identify a complex of external and internal relationships that have shaped the socio-economic, cultural, religious and value-orientation mindset of the Soviet generation.The main difference of the present study is the fact that its main objective is to study the history and role of economic and social institutions of education, upbringing, culture, and health of children in their transition to adulthood during the Russian Civil War.A comprehensive analysis of Russian and Soviet archives and publications of Russian and foreign scientists presented in the article made it possible to assess the influence of economic and social institutions (institutions of communication, institutions of one-man management in warfare, public education institutions) on the formation of the Soviet generation during the Civil War and postwar period in the Crimea Region.The results of the study will help to improve the existing system of scientific knowledge about the functions of the basic social and economic institutions through the prism of their adaptability properties with their adoption in any given economic system. A retrospective analysis of the transformation of the institutional environment of children's education and upbringing during the Civil War revealed an integrative relationship in the system of children's patriotic education of that period and the processes of establishing a new Soviet generation.Â Â